An improved asymmetric half-bridge converter for switched reluctance motor in low-speed operation with current regulated mode - Woothipatanapan, Sakhon; Chancharoensook, Phop; Jangwanitlert, Anuwat (My University, 2015)
This study presents a novel method for reducing the switching losses of an asymmetric half-bridge converter for a three-phase, 12/8 switched reluctance motor operated in low speed. In particular, this study aims to reduce the switching-off losses of chopping switches in the converter when operated in the current regulated mode (chopping mode). The proposed method uses the mixed parallel operation of IGBT (chopping switch) and MOSFET (auxiliary switch). MOSFET is precisely controlled to momentarily conduct prior to the turn-off interval of the IGBT. Consequently, the voltage across the switches is clamped to approximately zero, substantially decreasing the turn-off switching losses. The analytical expressions of power losses are extensively elaborated. Compared with the conventional asymmetric half-bridge converter, the modified converter can effectively minimize the switching losses. Therefore, the efficiency of the converter is eventually improved. Computer simulation and experimental results confirm the effectiveness of the proposed technique.
Keywords: Asymmetric half-bridge converter; Parallel IGBT/MOSFET; Switched reluctance motor; Switching loss